Sikap dan Pemertahanan Bahasa Ibu dalam Keluarga Bapak Muhlisin - Awaliyah, Novi Imroatul (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Language attitudes and language maintenance can be studied through a sociolinguistic approach based on individual speakers. Language attitudes are divided into two categories: positive and negative. A positive attitude is reflected in efforts to maintain a language by preserving it and feeling proud to use it. This can be observed in the family of Mr. Muhlisin, who have two different mother tongues. However, each member of the family strives to maintain their own mother tongue. Therefore, the data source used in this article is the utterances between two speakers within the family, collected through the observation method. The result of this study shows that Mr. Muhlisin's family demonstrates a positive language attitude and maintains their language in daily communication. Abstrak Sikap dan pemertahanan bahasa dapat dikaji melalui studi sosiolinguistik berdasarkan individu penutur bahasa. Sikap bahasa terbagi menjadi dua, sikap positif dan negatif. Sikap positif merupakan sikap mempertahankan bahasa dengan menjaga bahasa dan merasa bangga menggunakannya. Hal tersebut dapat ditemui dalam keluarga bapak Muhlisin yang memiliki dua bahasa ibu. Akan tetapi, dalam keluarga tersebut saling mempertahankan bahasa ibu masing-masing. Sehingga sumber data yang digunakan dalam artikel ini adalah tuturan antara dua penutur dalam keluarga tersebut dengan metode observasi. Hasil dari penelitian ini adalah keluarga bapak Muhlisin tergolong memiliki sikap positif dan mempertahankan bahasa dalam komunikasi.